PENERAPAN METODE PENILAIAN BERBASIS PORTOFOLIO DALAM MENINGKATKAN PEMBELAJARAN BAHASA INDONESIA - Bagus Mahardika (Jurusan PGMI FTIK IAIN Metro Lampung, 2018)
Assessment is one of the important stages in the learning process of Indonesia because through the assessment of teachers to know the extent to which the learning objectives have been achieved. Assessment can be done through measurement (quantitative description) and / or through non-measurement (qualitative description). When teachers collect information on students' level of understanding through questions, observations, and assignments the teacher actually has conducted a non-measurement evaluation. The activity of the teacher is very useful in determining the level of mastery of students and in assessing the effectiveness of the learning process. Accurate information about student learning outcomes, interests and needs can only be obtained through effective assessment and assessment. The current assessment is a portfolio assessment that has many benefits for both teachers and students. Portfolio assessment is broader than assessment through tests, as with portfolios, teachers can follow cognitive development, attitudes, interests and student activities related to math. Thus, teachers can utilize the portfolio in improving the quality of learning which in turn will improve the quality of student learning outcomes.